2007
DOI: 10.1002/jcp.21338
|View full text |Cite
|
Sign up to set email alerts
|

ESE‐1 is a potent repressor of type II collagen gene (COL2A1) transcription in human chondrocytes

Abstract: The epithelium-specific ETS (ESE)-1 transcription factor is induced in chondrocytes by interleukin-1β (IL-1β). We reported previously that early activation of EGR-1 by IL-1β results in suppression of the proximal COL2A1 promoter activity by displacement of Sp1 from GC boxes. Here we report that ESE-1 is a potent transcriptional suppressor of COL2A1 promoter activity in chondrocytes and accounts for the sustained, NF-κB-dependent inhibition by . Of the ETS factors tested, this response was specific to ESE-1, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
80
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 60 publications
(108 reference statements)
9
80
0
Order By: Relevance
“…It was also reported that Egr-1 inhibited interactions between CBP, Sp1, and TATA-binding proteins by interfering with Sp1 binding to the COL2A1 proximal promoter (37). ESE-1 was also reported to repress COL2A1 by Egr-1 through binding to the COL2A1 promoter (38). In Col2a1 regulation by C/EBP␤, C/EBP␤ may also interact with these co-factors, consequently inhibiting initiation of mRNA transcription in response to the inflammatory signal.…”
Section: Discussionmentioning
confidence: 98%
“…It was also reported that Egr-1 inhibited interactions between CBP, Sp1, and TATA-binding proteins by interfering with Sp1 binding to the COL2A1 proximal promoter (37). ESE-1 was also reported to repress COL2A1 by Egr-1 through binding to the COL2A1 promoter (38). In Col2a1 regulation by C/EBP␤, C/EBP␤ may also interact with these co-factors, consequently inhibiting initiation of mRNA transcription in response to the inflammatory signal.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, an induction of ESE-1 by IL-1b was found to occur in human chondrocytes, with ESE-1 functioning as a potent transcriptional suppressor of promoter activity for the type II collagen (COL2A1) gene and accounting for the sustained, NF-kB-dependent inhibition of COL2A1 expression by IL-1b. 68 Moreover, intracellular staining for ESE-1 was observed in chondrocytes from patients with osteoarthritis, but not in normal cartilage, suggesting a fundamental role for ESE-1 in cartilage degeneration and suppression of repair. 68 Substantial evidence for the involvement of ESE-1 in vascular inflammation has also been provided from many different studies.…”
Section: Ese-1 In the Corneal And Retinal Epithelium Of The Eyementioning
confidence: 97%
“…68 Moreover, intracellular staining for ESE-1 was observed in chondrocytes from patients with osteoarthritis, but not in normal cartilage, suggesting a fundamental role for ESE-1 in cartilage degeneration and suppression of repair. 68 Substantial evidence for the involvement of ESE-1 in vascular inflammation has also been provided from many different studies. For instance, ESE-1 has been shown to interact with the p50 subunit of NF-kB during the regulation of transcription of the inducible nitric-oxide synthase (NOS2) gene.…”
Section: Ese-1 In the Corneal And Retinal Epithelium Of The Eyementioning
confidence: 97%
“…Members of the Ets family that are located in the collagen promoter region are believed to be associated with collagen gene expression (35,40). Several ECM genes, including type I colla- gen, are regulated by Ets-1 (61).…”
Section: Discussionmentioning
confidence: 99%